Analysis of Soft Tissue Cephalometry in Skeletal Class I with Post Operation Unilateral and Bilateral CLP - Fitrianto, Ardan; Hamid, Thalca; Narmada, Ida Bagus (Faculty of Dental Medicine Universitas Airlangga, 2018)
Background: Facial appearance is an important diagnostic criterion that must be considered in orthodontics treatment plan. Orthodontics treatment is one of the dental treatments to prevent or correct tooth position abnormalities so that optimal function can be achieved including occlusion, proportional arrangement of the teeth and facial profile, as well as the harmony of facial profiles. Common facial abnormality cases include cleft lip and palate. Cleft lip and palate are caused by congenital defects and environmental factors. Purpose: The study was aimed to determine post-operative soft tissue cephalometric analysis of skeletal class I with post-operative of unilateral and bilateral CLP. Methods: This was a descriptive observational study. The subjects were secondary data from radiographic cephalometry obtained from the CLP Center Premier Hospital Surabaya and Universitas Airlangga Dental Hospital. Result: There was a significant difference in line angle parameters in both groups with a significant value of 0.002 (p <0.05). There were also significant differences in the Li-H line parameters in both groups with a significant value of 0.000 (p <0.05). There were H line angle and Li-H line differences in soft tissue cephalometric analysis between skeletal class I group with post-operative unilateral and bilateral CLP group. Conclusion: There was no difference in soft tissue cephalometric analysis between the post-operative of unilateral CLP and bilateral CLP on all parameters.